ANALISIS KEBERADAAN BUMDES SIMPAN-PINJAM DALAM MENINGKATKAN PENDAPATAN EKONOMI MASYARAKAT DESA TIMPUK KABUPATEN SEKADAU - Andre Ferdiansyah; Bambang Genjik S; F.Y Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study to determine the role of the existence of BUMDes Savingsand Loans in increasing the economic income of the community in Timpuk Village. Theproblem are: (1) How is the existence of Savings and Loan Village Owned Enterprisesin Increasing the Economic Income of the Timpuk Village Community? (2) How toIncrease Community Income through Savings and Loans Village Owned Enterprises inIncreasing the Economic Income of the Timpuk Village Community? This study useddescriptive research methods. Data collection techniques used are observation,interviews, and documentation. The results of this study indicate that (1) The Savingsand Loans BUMDes really help the Timpuk Village community to be able to increasetheir economic income with the capital provided and from the BUMDes activities itselfthere is nothing that harms the community, but adds income to help the communityincrease their income and increase the village's income. (2) The Savings and LoansBUMDes in Timpuk Village has been running in accordance with the applicable lawsand regulations, so that the community does not suffer losses with the interest expensegiven by the management.Keywords: BUMDes, Community Income